2019
DOI: 10.3390/metabo9060114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomics of Early Development of the Parasitic Plants Phelipanche aegyptiaca and Triphysaria versicolor

Abstract: Parasitic weeds of the family Orobanchaceae attach to the roots of host plants via haustoria capable of drawing nutrients from host vascular tissue. The connection of the haustorium to the host marks a shift in parasite metabolism from autotrophy to at least partial heterotrophy, depending on the level of parasite dependence. Species within the family Orobanchaceae span the spectrum of host nutrient dependency, yet the diversity of parasitic plant metabolism remains poorly understood, particularly during the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…However, the parasitism was found to have a markedly effect on metabolites change in the root metabolite for all genotypes compared to their respective noninfested control plants (Figure 5(B)). The changes in metabolomic profile was reported also by Clermont et al (2019) between the facultative parasite T. versicolor and the obligate holoparasite P. aegyptiaca with the host species M. Truncatula and A. thaliana, respectively. Similarly, other authors reported that the parasitism by P. aegyptiaca and O. foetida has affected respectively tomato (Amir 2016) and faba bean (Trabelsi et al 2017;Abbes et al 2020) metabolites when compared to non infested plants.…”
Section: Qualitative Untargeted Metabolomic Analysismentioning
confidence: 83%
See 3 more Smart Citations
“…However, the parasitism was found to have a markedly effect on metabolites change in the root metabolite for all genotypes compared to their respective noninfested control plants (Figure 5(B)). The changes in metabolomic profile was reported also by Clermont et al (2019) between the facultative parasite T. versicolor and the obligate holoparasite P. aegyptiaca with the host species M. Truncatula and A. thaliana, respectively. Similarly, other authors reported that the parasitism by P. aegyptiaca and O. foetida has affected respectively tomato (Amir 2016) and faba bean (Trabelsi et al 2017;Abbes et al 2020) metabolites when compared to non infested plants.…”
Section: Qualitative Untargeted Metabolomic Analysismentioning
confidence: 83%
“…Wang et al (2012) suggested that plant cells involve mechanical defense using sterols to make a physical barrier against the nutrient efflux to prevent nutrient and loss against bacterial and pathogens attack. In contrast to previous studies that focused more on polar metabolite variations including starch, amino acid and some secondary metabolite in response to parasitism in different plants (Abbes et al 2009;Amir 2016;Clermont et al 2019), the current study put the light-on fatty acids and sterols as important metabolites that can serve as regulatory pathways to conduct defense mechanisms in lentil and support the suggestion of the ability of the host plant to regulate phloem composition depending onthe host-parasite interaction (Jokinen and Irving 2019). Further, much remains unknown about the host-parasite biochemical interactions and a lot of work is still needed in exploring novel metabolic pathways and associated gene expression, genomic and proteomic analysis.…”
Section: Qualitative Untargeted Metabolomic Analysismentioning
confidence: 87%
See 2 more Smart Citations
“…5 and 6). Similarly, different studies reported the differential accumulation of metabolites in the parasitic plant from their hosts including free amino acids 43 , mannitol 44 , total soluble protein and phenolic compounds 34 , amino acids 45,46 , starch 47,48 . The parasite accumulates different metabolites when parasitizing different hosts, further support the assumption that the P. aegyptiaca may alter carotenoids obtained from the host and utilized these imported carotenoids for the synthesis of additional carotenoid compounds.…”
Section: Discussionmentioning
confidence: 96%